In silico docking studies of RP2 (X-Linked retinitis pigmentosa) protein using anthocyanins as potential inhibitors (Bangladesh Journal of Pharmacology, 2013)
Mutations occurring in X-Linked retinitis pigmentosa (RP2) gene causes retinal damage, ultimately leading to vision loss. Owing to the complications of the disease, there is no effective treatment till date. In the present study, we have refined the crystal structure of RP2 using protein preparation wizard of Glide software. Active site of the protein was predicted with SiteMap program. Five anthocyanin compounds from Syzygium cumini fruit peel were docked into the active site of RP2. Molecular docking calculations were performed by employing Glide XP algorithm. Cyanidin 3,5 diglucoside with lowest Gscore (-12.62 kcal/mol) was rescored subsequently with Prime-MMGBSA binding free energy calculations. Binding affinity (-93.62 kcal/mol) of the inhibitor suggests its potential use in the treatment of retinitis pigmentosa.